Systematic Literature Review: Strategies for Implementing Reading Writingg Connection in Indonesian Language Literacy Learning for Filipino Speakers - Dwi Novita Sari; Liza Septiani; Aninditya Sri Nugraheni (Journal of Education and Teacher Training Innovation, 2026)
The purpose of this study is to study how the relationship between reading and writing (RWC) is used in learning Indonesian literacy for Filipino speakers using the systematic literature review method. The research background stems from the need for BIPA learning in Philippine primary schools, which still emphasizes basic linguistic comprehension and more integrated reading and writing skills. The study investigated 200 articles and used the PRISMA model to select 10 relevant articles for 2020-2025 publications. The results of the study showed that strategies such as retelling, Cooperative Integrated Reading and Composition (CIRC), Think Talk Write (TTW), See, Write Fairy Tales (LICALIDO), the use of children's literature, and effective metacognitive approaches improve reading comprehension and writing ability simultaneously. Language acquisition and strengthening of cross-cultural literacy are assisted by the application of Indonesian cultural narrative texts. The result is that the integration of reading-writing through RWC benefits the development of Filipino students' basic literacy, especially when supported by digital media, contextual teaching materials, and the role of proficient teachers in implementing integrative strategies.